The Caucasus in the Years of Independence - Kobiashvili, Eka ("Intercultural Dialogues" Transactions, 2025)
The countries of the South Caucasus: Georgia, Armenia, and Azerbaijan, and the mountainous state in the North Caucasus - existed as neighboring, newly independent states during the First Republic of 1918 (1918–1921). Although they all shared a common past - being part of the Russian Empire - the relations between them were quite complex and contradictory. The article presents a brief overview of their relations during this period.